Dampak Kolaborasi antara Sekolah dan Masyarakat dalam Pemberdayaan Guru untuk Pembangunan Berkelanjutan - Muhammad Dliyauddin; Taufiqurrohman; Fatikha Rizqya Nur (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
School-community collaboration is another significant strategy used in the process of empowering teachers in order to promote sustainable development. Nevertheless, the previous school-community collaborations were mostly geared towards enhancing student learning experience, while the role played by school-community collaboration in promoting teachers' professional capacity is not well understood. Hence, this community service project sought to examine the effects of school-community collaboration on teacher empowerment in the promotion of sustainable development. This project was executed through needs assessment, planning of programs, collaboration activities, mentoring, monitoring, and evaluation. Data were collected through observations, interviews, questionnaires, and documentation, and analyzed qualitatively through data reduction, data presentation, and conclusion drawing procedures using source and technique triangulation methods to increase the validity of the results. From the study, it is evident that collaboration among schools, teachers, school committees, parents, and community members enhanced communication, improved stakeholders' participation, and promoted use of local resources as contextual learning tools. In addition, this program created a collaborative culture which was vital in promoting teachers' professional growth and development. As such, school-community collaboration can be considered as a sustainable model for empowering teachers.